Optimalisasi Kurikulum Dan Pengembangan Metode Pembelajaran di TPA Ar-Raudhah, Desa Beton, Siman, Ponorogo - Anshori, Hudan Ngisa; Septrianto, Wahyu; Ashari, Riza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to optimize the curriculum and develop learning methods at the Al-Qur'an Education Park (TPA) Ar-Raudhah, Beton Village, Siman District, Ponorogo Regency. TPA plays an important role in providing Islamic religious education to early childhood, but challenges in terms of implementing the curriculum and learning methods are still obstacles. Some of the problems faced include the lack of innovation in teaching methods, limited materials that are tailored to children's needs, and lack of learning motivation among students. For this reason, this study focuses on improving the existing curriculum and implementing more creative and interactive learning methods. The research method used is a qualitative approach with data collection techniques through observation, interviews, and literature studies. This study also involves the participation of TPA teachers and students to obtain a comprehensive picture of the ongoing learning process. The results of the study indicate that optimizing the curriculum that is tailored to the age and needs of children, as well as the use of more interactive learning methods such as play methods, audio-visual, and project-based learning, can increase motivation and effectiveness of learning at TPA Ar-Raudhah. The development of varied methods also helps improve children's understanding of the Qur'an and Islamic teachings. This study concludes that curriculum optimization and the development of more innovative learning methods are very important in improving the quality of education in TPA. The implementation of the results of this study is expected to be an effective teaching model for other TPAs, especially in facing the challenges of religious education for the younger generation in the modern era.